The Multi-Angle Scanning Method Application for X-Ray and Electron Beams Profiles Measurement; Electron, Positron, Neutron and X–ray Scattering under External Influences - Stuchebrov S. G. Sergey Gennadevich; Bulavskaya A. A. Angelina Aleksandrovna; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Miloichikova I. A. Irina Alekseevna (2021, 2021)
Title screen